Error Analysis and Enlightenment in Junior High School English Autonomous Writing - Yujie, Liu Shanshan Su (Advances in Social Sciences Research Journal, 2023)
English writing is one of the language output skills, which is the embodiment of the comprehensive use of English language ability of English learners. It is also the focus and difficulty of teachers in English teaching. Based on the theory of error analysis, this paper analyzes the common types of mistakes in junior middle school students’ English writing and their causes, and expounds how teachers improve junior middle school writing teaching for students’ common writing mistakes in order to help improve students’ English writing level.